ANALISIS PENGARUH BRAND IMAGE, HARGA, DAN REVIEW PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG PADA MAHASISWA UNDIP SEMARANG - Sintadi, Jason; Yoestini, Yoestini (Diponegoro Journal of Management, 2019)
Business competition of Samsung smartphone in Indonesia has increased rapidly in recentyears,in line with the emergence of new brands on the market. Existing companies arerequired to create strategies in order to survive and compete in the market. The purpose ofthis study is to determine the effect of brand image, price, and product review towardsSamsung smartphone’s purchase decision.The population in this study were Undip semarang students who have usedsmartphone from Samsung. The amount of sample used was 100 people selected usingaccidental sampling through questionnaire. Data obtain from the questionnaire were thenprocessed and analyzed using SPSS 23 program.The results of the study shows that brand image significantly influence the purchasedecision, the price significantly influence the purchase decision, and the product reviewsignificantly influence the purchase decision. The result of F test obtained a significancevalue smaller than 0,05, it can be concluded that the regression model produced is fit andproper to use. These result means that brand image, price, and product review can be usedto predict purchase decisions.